Books selection and collection strength - Hasan, Nur Azleen; Abdullah, Che Zainab (Human Resources Management Academic Research Society (HRMARS), 2018)
The issue of limited library collections is continuously voiced among the library users. Its include the issues of lacking of books, books are not suitable to students, and many others criticize come out from users. In relation to that, the strengths of books collections are doubt by users. The strengths of book collections depend on the selection process and criteria of books selection itself. This relate with the selection activities which involved the faculty team as selectors. This study presents the faculty attitudes in books selection pertaining to priority, intention and criteria consideration and its relationships with collections strength. Questionnaires were distributed to 320 random targeted respondents who involved in academic books selection. The analyses were undertaken using SPSS. Descriptive findings showed moderate results in three variables measured where the mean value was in the range 3.96 to 4.60 on a 5-point Likert. Besides that, the results also indicate a positive and moderate relationship between priority, intention, criteria consideration and collections strength. The insights of this study could be useful to library management in enhancing their collection building.